Evaluation of a 15-valent Pneumococcal Conjugate Vaccine in an Adult Rhesus Macaque Immunogenicity Model. (4th October 2017) - Xie, Jinfu; Kaufhold, Robin; Mcguinness, Debra; Zhang, Yuhua; Smith, William; Giovarelli, Cecelia; Winters, Michael; Musey, Luwy; Kosinski, Michael; Skinner, Julie
Abstract: Background: Streptococcus pneumoniae (pneumococcus) is a leading cause of a variety of diseases, including bacteremia, meningitis, and pneumonia, among older adults in the United States. Immunization with pneumococcal vaccines is an effective way to prevent these diseases. In this study, we evaluated the immunogenicity of 15-valent pneumococcal conjugate vaccine (PCV15) in adult rhesus macaques. Methods: Animals were intramuscularly immunized with PNEUMOVAX ® 23 and PCV15 vaccine (5 animals/group) and sera were collected before immunization and 30, 60, and 90 days after the immunization. Sera were assayed using multiplexed electrochemiluminescent (ECL) assays to measure serotype-specific IgG antibodies to all vaccine serotypes and multiplexed opsonophagocytic killing assays (MOPA) to measure functional antibody responses to 15 vaccine serotypes. Results: At day 30 post immunization, 16 out of the 23 serotypes in PNEUMOVAX 23 groups induced statistically significant higher ECL titers compared with pre bleed, ranging from 1.6-fold (19A) to 28.3-fold (15B). Compared with PNEUMOVAX 23, PCV15 induced much higher ECL titers. Thirteen out of the 15 serotypes in PCV15 groups induced statistically significant higher ECL titers compared with pre bleed, ranging from 7.4-fold (14) to 47.3-fold (4). The ECL antibody titers gradually decreased from day 30 to day 90 for both groups. We also compared the functional MOPA titers of the day 30 sera compared with pre bleed for 15 vaccine serotypes. Out of the 14 common vaccine serotypes, 7 serotypes in the PNEUMOVAX 23 immunized macaques had a >4 fold increase in MOPA titer, ranging from 4-fold (22F) to 3902-fold (33F) and 11 serotypes in the PCV15 immunized macaques had a >4-fold increase in MOPA titer, ranging from 6.3-fold (23F) to 4445-fold (7F). Twelve out of the 14 common serotypes in PCV15 group had higher MOPA titers compared with the PNEUMOVAX 23 group, although they didn't reach statistical significance due to high variability. Conclusion: These data demonstrate that a single dose of PCV15 is highly immunogenic in adult rhesus macaques and has better immunogenicity for most common serotypes compared with PNEUMOVAX 23. However, PNEUMOVAX 23 offers broader serotype coverage with 9 additional serotypes contained in the vaccine. Disclosures: J. Xie, Merck & Co. Inc: Employee, Salary; R. Kaufhold, Merck & Co. Inc: Employee, Salary; D. Mcguinness, Merck & Co. Inc: Employee, Salary; Y. Zhang, Merck & Co. Inc.: Employee, Salary; W. Smith, Merck & Co. Inc.: Employee, Salary; C. Giovarelli, Merck & Co. Inc.: Employee, Salary; M. Winters, Merck & Co. Inc: Employee, Salary; L. Musey, Merck & Co. Inc: Employee, Salary; M. Kosinski, Merck & Co. Inc: Employee, Salary; J. Skinner, Merck & Co. Inc: Employee, Salary